Mapping the Mind: Exploring Students' Visual-Spatial Thinking in Transformation Geometry - Gelar Dwirahayu; Gusni Satriawati; Dindin Sobiruddin; Bambang Avip Prianta; Tiara Sekar Harnum (MASI Mandiri Edukasi, 2025)
This study investigates high school students’ visual-spatial thinking ability in the context of transformation geometry using a descriptive quantitative design. A total of 241 students from public and Islamic high schools in Jakarta participated in the study, responding to a validated 40-item multiple-choice test assessing four key indicators: imagining, problem-solving, pattern seeking, and conceptualising. Results reveal that students generally performed at a medium level across all indicators, with the highest scores in imagining (M=62.97) and the lowest in conceptualising (M=47.05). These findings suggest that while students demonstrate some spatial reasoning capability, their conceptual understanding remains limited. The study highlights the importance of incorporating visualisation-focused strategies in geometry instruction to strengthen spatial reasoning and deeper comprehension of transformation concepts. Future research should explore the longitudinal impact of visual-spatial training and its role in developing higher-order geometrical thinking.